2021
DOI: 10.1001/jamainternmed.2020.7386
|View full text |Cite
|
Sign up to set email alerts
|

Association of Stratification by Proportion of Patients Dually Enrolled in Medicare and Medicaid With Financial Penalties in the Hospital-Acquired Condition Reduction Program

Abstract: Program (HACRP) is a value-based payment program focused on safety events. Prior studies have found that the program disproportionately penalizes safety-net hospitals, which may perform more poorly because of unmeasured severity of illness rather than lower quality. A similar program, the Hospital Readmissions Reduction Program, stratifies hospitals into 5 peer groups for evaluation based on the proportion of their patients dually enrolled in Medicare and Medicaid, but the effect of stratification on the HACRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…Additional information on hospital characteristics was obtained from the American Hospital Association Annual Survey for 2019. We followed the Centers for Medicare and Medicaid Services' recent approach 12,13 and considered hospitals in the highest quintile of dual enrollment among Medicare admissions to be safety-net hospitals, 14,15 and those in the highest quintile of the proportion of their Medicare admissions who were identified to be Black or Hispanic to be high-minority hospitals, following a similar convention. 14,16,17…”
Section: Hospital Characteristicsmentioning
confidence: 99%
“…Additional information on hospital characteristics was obtained from the American Hospital Association Annual Survey for 2019. We followed the Centers for Medicare and Medicaid Services' recent approach 12,13 and considered hospitals in the highest quintile of dual enrollment among Medicare admissions to be safety-net hospitals, 14,15 and those in the highest quintile of the proportion of their Medicare admissions who were identified to be Black or Hispanic to be high-minority hospitals, following a similar convention. 14,16,17…”
Section: Hospital Characteristicsmentioning
confidence: 99%
“…Audio recordings from the 1:1 interview from 25 participants were transcribed verbatim and analyzed independently by three members of the research team. Using the framework method of qualitive analysis 20 22 and iterative user-centered informed analysis, 10 19 10 themes emerged from the qualitative analysis of participant feedback ( Table 3 ). Primary takeaways from the thematic analysis revealed that participants learned to navigate the tool quickly moving from day 1 to 3 to evaluate MHACs potentially influenced by the removal of the IUC.…”
Section: Resultsmentioning
confidence: 99%
“…This framework also accounted for differences in these competing risks across patients with a variety of characteristics, including whether an IUC was present on admission, comorbidities, demographics (age, sex, race/ethnicity, and primary insurance), source of admission, and assessments of fall risk and HAPI risk, all of which are correlated with the risk of HACs. [20][21][22] A binary logistic specification was used for the probability of an event occurring on each patient-day and, given an event occurred on a patient-day, a multinomial logistic specification was used for the probability of each HAC. These logistic specifications provided a flexible empirical framework that accounted for the complex interactions between the timing of the decision to remove or reinsert an IUC and the occurrence of HACs.…”
Section: Methodsmentioning
confidence: 99%
“…Regional benchmarks in CJR may inadvertently serve an institutionalized function of penalizing the safety-net hospitals. 2 Policy makers should ensure that hospitals receive achievable spending benchmarks to avoid widening disparities in care. By design, CJR did not levy penalties in 2016.…”
Section: Jama Health Forum | Research Lettermentioning
confidence: 99%
“…1 Little is known about how Medicare distributed penalties under these policy changes. Given the disproportionate penalization of safety-net hospitals and hospitals serving Black and Hispanic patients under value-based payment, 2 , 3 understanding trends in their penalization status under CJR has important equity implications as Medicare expands bundled payment.…”
Section: Introductionmentioning
confidence: 99%